The strategy in teaching vocabulary through WordWall for engaging young learners in English Club of SD Negeri 2 Barabai Timur: Abstrack, Introduction, Method, Result and Discussion, Conclusion and Recommendation, References - Aminah, Siti; Yuliani, Novi Dwi; Isnaniah (Research and Innovation in Language Learning, 2025)
This study aims to describe the vocabulary teaching strategy employed by teachers using Wordwall in the English Club at SD Negeri 2 Barabai Timur and to analyze its classroom implementation and students' perceptions. Vocabulary mastery is fundamental in English learning, and interactive approaches are needed to support young learners. This research applied a qualitative field study, collecting data through observation, semi-structured interviews, questionnaires, and documentation. The participants were one instructor and 20 students of the English Club. Findings from the thematic analysis revealed that instructor employed various strategies such as contextual introduction, repetition, visualization, interactive games, thematic grouping, and formative quizzes. These strategy enhanced student engagement, improved vocabulary retention, and fostered a more enjoyable learning atmosphere. Furthermore, most students expressed positive perceptions of Wordwall, reporting increased motivation and confidence in learning English vocabulary. This study highlights the potential of integrating Wordwall not only as an interactive learning medium but also as an effective assessment tool, contributing to the development of engaging vocabulary teaching practices in elementary English learning contexts.